2015
DOI: 10.1016/j.jmmm.2014.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of driven nanorod transport through a biopolymer matrix

Abstract: Applying magnetic fields to guide and retain drug-loaded magnetic particles in vivo has been proposed as a way of treating illnesses. Largely, these efforts have been targeted at tumors. One significant barrier to long range transport within tumors is the extracellular matrix (ECM). We perform single particle measurements of 18 nm diameter nanorods undergoing magnetophoresis through ECM, and analyze the motion of these nanorods in two dimensions. We observe intra-particle magnetophoresis in this viscoelastic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Even at the IONP concentration of 200 mg/L, the number of nanorods present in the fluid was still on the very high side of 4 × 10 8 pts/ μL. Compared to the single nanorod experiment with a magnetophoretic velocity of 4.3 ± 2.9 μm/min, 41 conducted at low nanorod count of 1 × 10 3 pts/μL (particle-to-particle interaction was very minimum along the migration pathway, so no occurrence of cooperative magnetophoresis), the velocity that we observed here was 3000 times faster. Such huge differences indirectly confirmed that the particle we tracked in Figure 7 was undergoing cooperative magnetophoresis, and hence, the particle concentration effect plays an important role for any paper-based magnetophoretic technology development.…”
Section: ■ Experimental Sectionmentioning
confidence: 81%
“…Even at the IONP concentration of 200 mg/L, the number of nanorods present in the fluid was still on the very high side of 4 × 10 8 pts/ μL. Compared to the single nanorod experiment with a magnetophoretic velocity of 4.3 ± 2.9 μm/min, 41 conducted at low nanorod count of 1 × 10 3 pts/μL (particle-to-particle interaction was very minimum along the migration pathway, so no occurrence of cooperative magnetophoresis), the velocity that we observed here was 3000 times faster. Such huge differences indirectly confirmed that the particle we tracked in Figure 7 was undergoing cooperative magnetophoresis, and hence, the particle concentration effect plays an important role for any paper-based magnetophoretic technology development.…”
Section: ■ Experimental Sectionmentioning
confidence: 81%
“…Gold-tipped iron microdevices were synthesized in anodized aluminum oxide (AAO) templates via template guided electrodeposition following established protocols [8]- [10]. Briefly, AAO templates (Whatman Anodisc, nominal pore diameter 0.2 µm) were coated with 0.5 µm silver via thermal evaporation, forming a working electrode.…”
Section: A Magnetic Microdevicesmentioning
confidence: 99%
“…4,5 Transport of particles in living tissue is governed by particle size, surface chemistry, 6 and the biological barriers. For capture applications, large particles have disadvantages in the complex biopolymer network comprising tissue arising from their size, 7 including potential exclusion or reduced extraction efficiencies due to entanglements/drag forces. Suspensions of individual superparamagnetic nanoparticles (MNPs) have possible advantages for this application.…”
Section: ■ Introductionmentioning
confidence: 99%